Monetary aggregates to improve early output gap estimates in the euro area: An empirical assessment - Jens Boysen-Hogrefe (Kiel Institute for the World Economy (IfW), 2014)
Output gap estimates at the current edge are subject to severe revisions. This study analyzes whether monetary aggregates can be used to improve the reliability of early output gap estimates as proposed by several theoretical models. A real-time experiment shows that real M1 can improve output gap estimates for euro area data. For many periods the cyclical component of real M1 shows good results, while a forecasting strategy based on projecting GDP series seems to be more robust and provides superior results during the Great Recession. Broader monetary aggregates provide no superior information for output gap estimates.
Keywords: E32; E37; E41; E58; 330; output gap; real-time data; M1; M3; euro area; money cycle